Pengaruh Environmental Concern dan New Environmental Paradigm Terhadap Pro-Environmental Behavior Peserta Didik Sma Negeri di Jakarta - Gebby Chrislia Puspaningrum; I Made Putrawan; Refirman Djamahar (IJEEM - Indonesian Journal of Environmental Education and Management, 2023)
The increase in ecological crises occurs due to the lack of human awareness in protecting the environment. Efforts to overcome this by increasing pro-environmental behavior among students as the next generation. This study aimed to determine the effect of environmental concern and the new environmental paradigm toward students' pro-environmental behavior. The research was conducted at SMAN 54 Jakarta in the odd semester of the 2022/2023 school year with a sample of 100 students. The method used is a survey method through causal studies and analyzed by path analysis. The results of this research indicate that environmental concern has a direct effect on the new environmental paradigm significantly, the new environmental paradigm has a direct effect on pro-environmental behavior significantly, environmental concern has a direct effect on pro-environmental behavior significantly and environmental concern has an indirect effect on pro-environmental behavior through the new environmental paradigm significantly. Keyword: path analysis, environmental concern, new environmental paradigm, pro-environmental behavior, students